ANALYSIS OF COMMON-SIZE IMPLEMENTATION IN SHARIA FINANCIAL REPORTING - SALEH, MUHAMMAD AMIN (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2025)
The implementation of common-size analysis in Sharia financial reporting offers an effective approach to enhancing the transparency, comparability, and consistency of financial statements in Islamic financial institutions. This study analyzes how the application of common-size techniques contributes to the quality and clarity of Sharia-compliant financial disclosures. Using a qualitative descriptive method with a case study approach, the research explores the practical aspects and implications of implementing common-size analysis within selected Islamic financial institutions. The findings indicate that common-size analysis supports better financial interpretation, facilitates benchmarking across periods or institutions, and improves overall stakeholder understanding. Moreover, it strengthens external trust by ensuring that financial reports are more accessible and informative. This study highlights the importance of adopting analytical tools such as common-size techniques to advance the practice and credibility of Sharia financial reporting.